Automatic Concept Maps Generation in Support of Educational Processes - Arianna Pipitone; Vincenzo Cannella; Roberto Pirrone (Je-LKS: Journal of E-Learning and Knowledge Society, 2014)
A VLE is a system where three main actors can be devised: the teacher in the role of instructional designer, the tutor, and the stu- dent. Instructional designers need easy interaction for specifying the course domain structure to the system, and for controlling how well the learning materials agree to such a structure. Tutors need tools for having a holistic perception of the evolution of single students and/or groups in the VLE during the learning process. Finally, students need self regulation in terms of controlling their learning rate, reflect on their learning strategies, and comparing with other people in the class. In this work we claim that sharing an implicit representation of the knowledge about the course domain between all these actors can meet the requirements stated before, and we present a tool that has been developed as part of the I-TUTOR project according to our claim. The tool analyzes a suitable document corpus describing the course domain, and generates a semantic space, which in turn is displayed as a 2D zoomable map. All the relevant concepts of the domain are depicted in the map, and learning materials can be browsed through the tool. Also the texts generated by students during the learning process as well as their social activities inside the VLE can be placed in the map. The motivations of the work are reported as well as the underlying AI techniques, and the whole system is explained in detail.